Intercultural City in the Context of a Polyethnic Community Governing - Afanasieva, Lyudmila; Bukrieieva, Iryna; Glyns’ka, Lyudmila; Orlov, Andrii; Hlebova, Natalia Ivanivna (Journal of History Culture and Art Research, 2020)
A distinctive feature of modern civilization is the cultural heterogeneity of societies. Industrial mode of production processes, wars and conquests, various forms of migration, democratization processes, and trends of openness served as the basis for the formation of modern multiethnic and multicultural nations. In the context of the processes of modernization of modern society, the deep transformation of culture and complex intercultural relations, the problem of mutual understanding and interaction between representatives of different cultures has acquired great significance. In today’s world, the population of many states and cities is becoming multicultural. One of them is the Ukrainian multicultural city Melitopol. The article analyzes the principles of interculturalism as a modern approach to the policy of managing the cultural diversity of Melitopol, developed by the Council of Europe in the program “Intercultural Cities”. The main idea of the program is the understanding of the concept of diversity benefits, based on the perception of migrants, refugees, representatives of different cultures, their languages and beliefs as a development resource, and not just as a vulnerable group only requiring the state support. The program aims to develop a local intercultural policy by attracting representatives of ethnic groups step by step to an active public life and community governance. Interculturalism emphasizes the need to ensure the survival and prosperity of each culture and seeks to enhance intercultural interaction as a means of building trust and society strengthening. The program aims to combine the efforts of politicians, government officials, business representatives, various qualified specialists, citizens, and even the media to create a city that is proud of its diversity and strengthens it in every aspect. The article presents the following steps to develop an intercultural strategy for the multi-ethnic Melitopol: public opinion monitoring, content analysis of local media publications, methods of positive segmentation, focus group research in the World café format, and design thinking. The research justifies why it is important to use sociological support while forming an intercultural competence, defining it as a means of identifying the relevance of global public self-government principles to the democratic development of modern Ukrainian urban communities.